Noninvasive Ambulatory Hemodynamic Monitoring Based on Electrocardiogram and Impedance Cardiography (Journal of Fiber Bioengineering and Informatics, 2015)
Two different noninvasive ambulatory hemodynamic monitoring devices (belt-type and chest-type) based\ron Electrocardiogram (ECG) and Impedance Cardiography (ICG) has been designed, fabricated and\rtested. Hardware designs of the two ambulatory hemodynamic monitoring devices based on Tetrapolar\rconfiguration and placement of the electrodes were introduced. Hemodynamic parameters such as Stroke\rVolume (SV), Cardiac Output (CO) and Cardiac Index (CI) can be estimated according to Kubicek\rFormula by extracting characteristic points and characteristic periods in the ICG Signal. CI is CO\rdivided by body surface area. CI is comparable among different people because it is not influenced\rby the body height and weight. The body's physiological responses to postural change are primarily a\rreaction to the change of gravity, because change of gravity can cause changes of blood flow distribution\rin organs and tissues. Different body postures (upright or supine) can result in reducing or rising of\rCO. The detection accuracy has also been validated with a commercial ICG detection instrument from\rMindray company, and the correlation coefficient is 0.83.
Keywords: Electrocardiogram; Impedance Cardiography; Noninvasive Ambulatory Hemodynamic Monitoring; Characteristic Points; Cardiac Output; Cardiac Index; Postural Change